The Effect of Realistic Mathematical Approaches and Learning Independence on Students' Mathematical Communication Ability SD Negeri Cot Meuraja - Herlin Fitria; Edy Surya; Naeklan Simbolon (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to determine: (1) To determine the differences in mathematical communication of students who are taught using a realistic mathematical approach compared to conventional approaches; (2) To determine the differences in mathematical communication skills of students who have high learning independence compared to students who have low learning independence; and (3) To determine the interaction between realistic mathematical approaches and independent learning on students' mathematical communication skills. This research was conducted at SD Negeri Cot Meuraja. The research method used is quantitative with a quasi-experimental research type. Data collection techniques used questionnaires and tests. The data analysis technique in this study used the Two Way Anova test. The results showed that: (1) The mathematical communication skills of students who are taught with a realistic mathematical approach are higher than conventional approaches (Fcount = 23.476 and sig. 0.000> 0.05); (2) The mathematical communication skills of students who have high learning independence are higher than students who have low learning independence (Fcount = 7.673 and sig. 0.008> 0.05).